A new fossil Eurypinae genus and sexual dimorphism in the representatives of Omineus (Coleoptera: Mycteridae) from Tertiary amber of Europe - Alekseev, Vitalii Igorevich; Bukejs, Andris; Pollock, Darren Andrew (Zootaxa, 2020)
Europoeurypus inglaeso gen. et sp. nov. is described from Eocene Baltic amber found on the Sambian Peninsula, Kaliningrad Region, Russia. Four additional specimens of mycterid beetles from collections of Baltic amber are reported. The secondary sexual characters and sexual dimorphism in the Eocene representatives of the genus Omineus Lewis, 1895 are documented for the first time and examined using X-ray micro-computed tomography (μCT). The studied Omineus male specimens were attributed to the fossil species Omineus febribilis Alekseev, Pollock & Bukejs, 2019. A key to fossil species of Eurypinae from Eocene ambers is provided and several aspects of the biogeography of the subfamily Eurypinae are discussed.